A CuNiSn-based high entropy alloy nanopowder for CO2 electrocatalytic reduction

By introducing Fe and Bi into CuSnNi ternary alloy and preparing CuSnNi-based high-entropy alloy nanopowder by liquid phase reduction method, the problems of high production costs, large particle sizes and few product types of existing high-entropy alloy materials are solved, and efficient CO2 electrocatalytic reduction and low-cost production are achieved.

CN118745546BActive Publication Date: 2025-03-21CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410962127.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2025-03-21
Estimated Expiration
2044-07-18

AI Technical Summary

Technical Problem

The existing high-entropy alloy materials for CO2 electrocatalysis have high production costs, large particle sizes and few product types, making it difficult to meet the practical application needs.

Method used

CuSnNi ternary alloy was used as the basic alloy, and non-precious metal elements Fe and Bi were introduced into the alloy at the same time, and CuSnNi-based high-entropy alloy nanopowder was prepared by liquid phase reduction method to obtain high-entropy alloy nanopowder with uniform element distribution, small particle size and narrow distribution width.

Benefits of technology

Efficient CO2 electrocatalytic reduction is achieved to generate C2 products that are difficult to produce in traditional metal catalysts, such as ethylene and ethane, while reducing production costs and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118745546B_ABST
    Figure CN118745546B_ABST
Patent Text Reader

Abstract

The invention discloses a CuSnNi-based high entropy alloy nanopowder for CO2 electrocatalytic reduction. The high entropy alloy of the invention is based on a CuSnNi ternary alloy, and non-precious metal elements Bi and Fe are added to the system. A liquid phase reduction method is used to synthesize a high entropy alloy nanopowder with uniform element distribution, small particle size and narrow distribution width. The high entropy alloy nanopowder has the advantages of high specific surface area, rich void structure, multiple active sites, stable microstructure, good dispersibility and low preparation cost. When applied to CO2 electrocatalytic reduction, it exhibits high catalytic activity and excellent stability under weak alkaline conditions, and the obtained products are rich in variety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of special metal powder preparation, and in particular relates to a CuNiSn-based high entropy alloy nano powder for CO2 electrocatalytic reduction. Background Art

[0002] With the progress of industrialization, fossil fuels such as coal, oil and natural gas have become the main energy sources to promote the development of human society and economy. However, the huge consumption of fossil fuels produces a large amount of carbon dioxide gas, causing environmental problems such as the greenhouse effect. As an economical, safe and sustainable carbon-oxygen resource compound, carbon dioxide has great development potential in converting it into liquid fuels and chemicals. Among them, the electrocatalytic reduction of carbon dioxide can generate fuels and chemicals such as carbon monoxide, formate, hydrocarbons or alcohols. Therefore, the electrocatalytic reduction of carbon dioxide can not only "turn waste into treasure" and reduce CO2 emissions, but also convert renewable energy into high-energy-density fuel storage or chemicals, which has important strategic significance and economic value.

[0003] Electrocatalysts play a vital role in the efficiency and other properties of carbon dioxide electrocatalytic reduction. At present, carbon dioxide reduction electrocatalyst materials mainly include metal catalysts, non-metallic catalysts and molecular catalysts. Among them, polycrystalline single metal catalysts have received extensive attention in the early stage of research because of their simple structure, good conductivity and easy processing. However, due to the small specific surface area of ​​polycrystalline single metal catalysts, their electrocatalytic efficiency is not ideal. In order to improve the catalytic efficiency, scientists have further developed metal catalyst materials with nanostructures, which effectively increase the specific surface area of ​​the catalyst and increase the number of surface active sites, thereby improving its electrocatalytic efficiency; and the surface of nanostructured metal catalysts contains a large number of edge / low coordination sites, which makes it behave differently from bulk metals and can regulate the activity and product selection during CO2 reduction. In addition, there are bimetallic catalysts prepared in the prior art, such as Au-Cu alloys and Ag-Sn alloys, which also effectively improve the electrocatalytic efficiency of carbon dioxide. However, traditional metal catalytic materials are mainly precious metal materials such as Au, Ag, Pt, Pd, etc., which result in relatively high production costs and limit their practical applications.

[0004] The composition and structure of high-entropy alloys can be adjusted according to application requirements. In thermodynamics, they have a "high-entropy effect" that can promote the formation of high-entropy solid solutions; in microstructure, they have a "lattice distortion effect" that can cause solid solution strengthening and increase strength; in terms of performance, they have a "cocktail effect" that is conducive to the comprehensive optimization of various properties of the alloy. Therefore, high-entropy alloys have excellent properties that traditional alloys do not have.

[0005] High entropy alloys have great application potential in the field of electrocatalysis. In the prior art, AuAgPtPdCu high entropy nanocrystalline catalysts (Nellaiappan S, Katiyar NK, Kumar R, et al. High-Entropy Alloys as Catalysts for the CO2 and CO Reduction Reactions: Experimental Realization [J]. ACS catalysis, 2020, 10 (6): 3658-3663.) were prepared, showing excellent CO2 electrocatalytic reduction performance, and the results showed that the electrocatalytic activity was mainly described by the presence of redox active copper metal, and other metals provided synergistic effects. However, the catalytic high entropy alloy materials reported in the current patents are mainly used for water electrolysis or fuel cells, and most of them contain precious metal elements; and no related patents for high entropy alloys for CO2 electrocatalysis have been reported. In addition, the preparation methods of high entropy alloys are mainly concentrated in high-temperature melting methods such as arc melting, zone melting and laser cladding, which have high energy consumption, high production costs, and the products are mainly bulk materials, and micro-nano-sized high entropy alloys cannot be prepared. Summary of the invention

[0006] In view of the problems of high production cost, large particle size and few product types of high entropy alloys for CO2 electrocatalysis in the prior art, the purpose of the present invention is to provide a CuSnNi-based high entropy alloy nanopowder for CO2 electrocatalytic reduction. The present invention simultaneously introduces two non-metallic elements, Fe and Bi, and adopts a liquid phase reduction method to obtain an alloy powder with advantages such as uniform element distribution, small particle size and narrow distribution width, rich void structure and many active sites. In addition, the CuSnNi-based high entropy alloy nanopowder of the present invention is used as a catalyst in the CO2 electrocatalytic reduction reaction, which not only shows high catalytic activity and excellent stability, but also can generate C2 products that are difficult to generate with traditional metal catalysts.

[0007] In order to achieve the above technical objectives, the present invention provides a CuSnNi-based high entropy alloy nanopowder for CO2 electrocatalytic reduction, which is composed of the following components in terms of molar percentage: Cu 15-25%, Sn 15-25%, Ni 15-25%, Fe 15-28%, and Bi 15-28%; the high entropy alloy nanopowder is obtained by adding a protonic acid to a precursor solution to maintain acidic conditions, and then adding a reducing agent to sequentially carry out a reduction reaction, purification treatment, and drying; the precursor solution is obtained by mixing and dissolving at least one selected from iron salts and ferrous salts with copper salts, tin salts, nickel salts, and bismuth salts; the CuSnNi-based high entropy alloy nanopowder is used as a catalyst for CO2 electrocatalytic reduction to generate C2 products.

[0008] The key to the technical solution of the present invention is to use CuSnNi ternary alloy as the basic alloy, and to introduce non-precious metal elements Fe and Bi into the alloy at the same time. The introduction of Fe and Bi elements forms a high entropy alloy, which can provide more structural dislocations (active sites) for electrocatalysis, and obtain a nearly continuous distribution of adsorption energy curves, thereby significantly improving the performance of electrocatalytic synthesis gas generation. In addition, the introduction of Fe elements is conducive to the formation of carbon-carbon bonds under electrocatalysis, and Bi elements can promote the formation of carbon-hydrogen bonds under electrocatalysis. Under the synergistic effect of the five metal elements in the above-mentioned high entropy alloy, when CuSnNiFeBi is used as a catalyst, electrocatalysis can obtain C2 products (such as ethane, ethylene) that are difficult to generate under traditional metal catalysis. At the same time, the content of each metal element in the high entropy alloy needs to be comprehensively controlled, because the level of its content will directly affect the microstructure, active sites and electrocatalytic CO2 reduction performance of the high entropy alloy.

[0009] Another key of the present invention is to use a liquid phase reduction method to prepare CuSnNi-based high entropy alloy nanopowders. The present invention is based on the principle of atomic size and lattice structure matching, and uses an ion aqueous solution of the required alloy metal element as a precursor. By comprehensively controlling the proportion of metal elements, the nucleation and growth process of particles can be regulated at the atomic and molecular level; secondly, by adding proton acid to keep the system in acidic conditions, the precipitation of metal ions can be inhibited, and finally, under the action of a reducing agent, high entropy alloy particles with more uniform particle size and nanometer size are obtained. Compared with the traditional preparation method of high entropy alloys, the preparation method of the present invention has low energy consumption, low cost and is easier to mass produce.

[0010] As a preferred solution, the total concentration of all metal salts in the precursor solution is 10 -4 ~10 -1 molL -1 , more preferably 10 -3 ~10 -4 mol L -1 .

[0011] As a preferred embodiment, the molar ratio of the copper salt, tin salt, nickel salt and bismuth salt is 2+ Sn 2+ 、Ni 2+ and Bi 3+ The molar ratio of Cu is 1:(0.5 to 2):(0.5 to 2):(0.5 to 1). More preferably, Cu 2+ Sn 2+ 、Ni 2+ and Bi 3+ The molar ratio is 1:1:1:(0.5~1).

[0012] As a preferred embodiment, the molar ratio of the total molar amount of the iron salt and the ferrous salt to the copper salt is as follows:3+ and Fe 2 + Total molar amount and Cu 2+ The molar ratio is (0.5-2):1.

[0013] The inventors found that the amount of each metal element has a direct impact on the catalytic performance of the alloy powder; among them, copper ions are the main catalytic active center. When the amount is too low, not only does it cause H2 to be the main gas in the synthesis gas, but also the content of other types of gases will decrease significantly; when the amount of nickel ions and tin ions is too low, they cannot form a synergistic effect with copper ions, which also causes H2 to be the main gas in the synthesis gas, and the content of other types of gases will decrease; when the amount of iron ions or ferrous ions is too low, it is not conducive to the formation of carbon-carbon bonds, resulting in a significant decrease in the content of C2 products in the electrocatalytic product or even the inability to generate C2 products; and when the amount of bismuth ions is too low, it is not conducive to the formation of carbon-hydrogen bonds, resulting in a significant decrease in the content of methane and C2 products in the electrocatalytic product or even the inability to generate such products. In addition, when the amount of metal ions is within the range selected by the present invention, the particle size distribution of the prepared alloy is narrower.

[0014] As a preferred solution, the protonic acid includes at least one of hydrochloric acid, hydrobromic acid, sulfuric acid, nitric acid and phosphoric acid, and the amount of the protonic acid is 1‰ to 10% of the total molar amount of metal ions in the metal salt. The amount of protonic acid added in the present invention is mainly to adjust the pH of the system under acidic conditions. It is further preferred that the protonic acid is hydrochloric acid and / or sulfuric acid, and the amount is 1% to 5% of the total molar amount of metal ions in the metal salt.

[0015] As a preferred solution, the acidic condition is to control the pH to 4-5. In the pH range selected by the present invention, the hydrolysis and precipitation of metal ions can be effectively inhibited, especially Fe 3+ , Fe 2+ and Cu 2+ , which is beneficial to the subsequent reduction effect of metal ions.

[0016] As a preferred solution, the reducing agent includes at least one of LiBH4, NaBH4 and KBH4, and the ratio of the amount of reducing agent to the total molar amount of metal ions in the metal salt is (2-50):1. The reducing agents selected in the present invention all have strong reducing properties. During use, some reducing agents will react with water and compete with the reduction reaction of metal ions in the present invention. However, the amount of reducing agent added in the present invention is much higher than the theoretical value of the amount of reducing agent substance required to reduce the metal salt, and the reaction activity of metal ions with NaBH4 is higher than the reaction activity of H2O with the reducing agent, so that the metal ions are fully reduced to ensure the formation of the high entropy alloy of the present invention. It is further preferred that the reducing agent is LiBH4 and / or NaBH4, and the ratio of the amount of reducing agent to the total molar amount of metal ions in the metal salt is (30-50):1. In the present invention, too low an amount of reducing agent added will lead to insufficient reduction of metal ions, affecting the proportion of alloy elements and catalytic performance; while too high an amount of reducing agent added will lead to excessively violent reactions, affecting the microscopic morphology of the alloy, and thus also affecting the catalytic performance of the alloy. The reduction mechanism of the reducing agent used in the present invention is: using BH4 in the reducing agent - The strong reducing property of the ions reduces the metal to form nuclei quickly and uniformly. At the same time, some of them react with water to form hydrogen bubbles, which can protect the metal particles from oxidation and growth, thereby obtaining alloy particles with a narrow particle size distribution.

[0017] As a preferred solution, the reduction reaction conditions are: temperature of -20 to 80°C, time of 0.5 to 8 hours, more preferably, temperature of 20 to 30°C, time of 2 to 4 hours.

[0018] As a preferred solution, the purification treatment adopts centrifugal purification, and the conditions of centrifugal purification are: the centrifugal speed is 5000-20000rpm, and the number of centrifugation is 2-8 times. More preferably, the centrifugal speed is 8000-10000rpm, and the number of centrifugation is 2-3 times. The purpose of centrifugal purification in the present invention is to remove the by-products alkali metal salts and borates generated by reduction and a small amount of raw materials.

[0019] As a preferred solution, the drying conditions are: temperature of 20-80°C and time of 0.5-72 hours, more preferably temperature of 50-70°C and time of 16-32 hours.

[0020] As a preferred solution, the specific surface area of ​​the high entropy alloy nanopowder is 50 to 200 m 2 g -1 The high entropy alloy nanopowder of the present invention has uniform element distribution, small particle size and narrow distribution width, and has the characteristics of high specific surface area, rich void structure, multiple active sites, stable microstructure, good dispersibility and low preparation cost. It is further preferred that the specific surface area is 60 to 100 m2 g -1 The particle size is 20-30 nm and can be dispersed in polar solvents such as ethanol, propanol, isopropanol, tetrahydrofuran and N,N-dimethylformamide.

[0021] The CuSnNi-based high entropy alloy nanopowder of the present invention is used as a catalyst for CO2 electrocatalytic reduction, and its reduction products cover a wide range of types such as synthesis gas, formate and methane, etc., especially C2 products that are difficult to generate with traditional metal catalysts, such as ethylene and ethane.

[0022] As a preferred solution, the specific process of the application to CO2 electrocatalytic reduction is: using a three-electrode system, using carbon paper loaded with electrocatalyst as a working electrode, using a ruthenium-iridium-titanium electrode as a counter electrode, and using a saturated Ag / AgCl electrode as a reference electrode; using a KHCO3 solution as an electrolyte; using a Nafion membrane as an ion-selective diaphragm; setting the electrocatalytic test potential to -1.3 to -1.5V (vs.Ag / AgCl). The CuSnNi-based high entropy alloy nanopowder of the present invention is ultrasonically mixed with propanol / ethanol / water and Nafion solution as an electrocatalyst, and then drop-coated on carbon paper as a working electrode to perform a CO2 electrocatalytic reduction performance test.

[0023] As a preferred solution, the CuSnNi-based high entropy alloy nanopowder is used in a weakly alkaline electrolyte in the CO2 electrocatalytic reduction reaction, and exhibits high catalytic activity and excellent stability under this condition. Further preferably, it exhibits high catalytic activity and excellent stability in an electrolyte with a pH of 8 to 10.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0025] (1) The present invention uses CuSnNi ternary alloy as the base alloy, and simultaneously introduces non-precious metal elements Fe and Bi into the alloy. Through the synergistic effect between the metal elements, the alloy has multiple active sites. When applied to the CO2 electrocatalytic reduction reaction, it not only exhibits high catalytic activity and excellent stability, but also can generate C2 products that are difficult to generate with traditional metal catalysts.

[0026] (2) The present invention adopts a liquid phase reduction method to prepare CuSnNi-based high entropy alloy nanopowder, which has the advantages of mild and controllable reaction conditions, high efficiency and low energy consumption. The nucleation and growth process of particles can be regulated at the atomic and molecular levels. The obtained high entropy alloy powder has uniform element distribution, small particle size and narrow distribution width, rich void structure, stable microstructure and good dispersibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1The microstructure and element distribution diagram of the alloy nanopowder prepared in Example 1 of the present invention, wherein (a) is a scanning electron microscope image; (b-f) are element distribution conditions tested by an energy dispersive X-ray spectrometer.

[0028] Figure 2 The microstructure and element distribution diagram of the alloy nanopowder prepared in Example 2 of the present invention, wherein (a) is a scanning electron microscope image; (b-f) are element distribution conditions tested by an energy dispersive X-ray spectrometer.

[0029] Figure 3 The microstructure and element distribution diagram of the alloy nanopowder prepared in Example 3 of the present invention, wherein (a) is a scanning electron microscope image; (b-f) are element distribution conditions tested by an energy dispersive X-ray spectrometer.

[0030] Figure 4 The stability test results of the alloy nanopowder prepared in Example 1 of the present invention as an electrocatalyst for catalytic CO2 reduction.

[0031] Figure 5 Gas chromatography results comparing the types of electrocatalytic CO2 reduction products at a potential of -1.5 V using the alloy nanopowders prepared in Example 1 of the present invention and Comparative Examples 1 to 3 as catalysts, wherein (a) is Comparative Example 1; (b) is Comparative Example 2; (c) is Comparative Example 3; and (d) is Example 1.

[0032] Figure 6 The gas chromatography results of the types of products of electrocatalytic CO2 reduction at a potential of -1.5V using the alloy nanopowder prepared in Comparative Example 4 of the present invention as a catalyst. DETAILED DESCRIPTION

[0033] The present invention is further described below in conjunction with examples. It should be understood that the following examples are only exemplary descriptions and explanations of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies realized based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0034] Unless otherwise specified, all reagents and raw materials used in the present invention are commercially available products or products that can be prepared by known methods.

[0035] Example 1

[0036] Weigh CuCl2·2H2O, SnCl2·2H2O, NiSO4·6H2O, Bi(NO3)3·5H2O, FeCl2·4H2O, (Cu 2+ Sn 2+ 、Ni 2+ 、Bi 3+ and Fe 2+The molar ratio of the five metal ions is 1:1:1:1:1, and the total molar amount of the five metal ions is 0.2mmol) is dissolved in 150ml of deionized water, and an appropriate amount of hydrochloric acid is added to adjust the pH value to 5 to prevent hydrolysis to form solution A; NaBH4 (8mmol) is dissolved in 50ml of deionized water to form solution B. At 25°C, solution B is slowly added to the stirred solution A, and stirring is continued for 2 hours. The resulting suspension is centrifuged and washed, first washed three times with deionized water, and then washed three times with ethanol. The washed crude product is vacuum dried (60°C, 24h) to obtain CuSnNiBiFe high entropy alloy powder, wherein Cu 17.0%; Sn 17.0%; Ni 22.2%; Bi 20.7%; Fe 23.0%.

[0037] Its microstructure and element distribution are as follows Figure 1 As shown in the figure, the prepared alloy nanopowder has a small particle size and each metal element is evenly distributed in the material. The specific surface area of ​​the alloy is 65m 2 / g, the particle size range is 20~50nm, and the particle size distribution is narrow.

[0038] Example 2

[0039] Weigh CuCl2·2H2O, SnCl2·2H2O, NiSO4·6H2O, Bi(NO3)3·5H2O, FeCl2·4H2O, (Cu 2+ Sn 2+ 、Ni 2+ 、Bi 3+ and Fe 2+ The molar ratio of the five metal ions is 1:1:1:0.8:1, and the total molar ratio of the five metal ions is 0.2 mmol), and the other conditions and steps are consistent with those in Example 1 to obtain CuSnNiBiFe high entropy alloy powder, wherein Cu 17.5%; Sn 18.0%; Ni 23.8%; Bi 16.2%; Fe 24.5%.

[0040] Its microstructure and element distribution are as follows Figure 2 As shown, the prepared alloy nanopowder has a small particle size and each metal element is evenly distributed in the material.

[0041] Example 3

[0042] Weigh CuCl2·2H2O, SnCl2·2H2O, NiSO4·6H2O, Bi(NO3)3·5H2O, FeCl2·4H2O, (Cu 2+ Sn 2+ 、Ni 2+ 、Bi 3+ and Fe 2+The molar ratio of the five metal ions is 1:1:1:1:0.8, and the total molar ratio of the five metal ions is 0.2 mmol). The other conditions and steps are the same as those in Example 1 to obtain CuSnNiBiFe high entropy alloy powder, wherein Cu 18.5%; Sn 19.1%; Ni 23.0%; Bi 22.4%; Fe 17.0%.

[0043] Its microstructure and element distribution are as follows Figure 3 As shown, the prepared alloy nanopowder has a small particle size and each metal element is evenly distributed in the material.

[0044] Comparative Example 1

[0045] The difference between this comparative example and Example 1 is that only CuCl2·2H2O, SnCl2·2H2O, NiSO4·6H2O (Cu 2+ Sn 2+ 、Ni 2+ The molar ratio of the three metal ions is 1:1:1, and the total molar ratio of the three metal ions is 0.2 mmol), and the other conditions and steps are the same, to obtain a CuSnNi alloy powder containing 34.2% Cu, 29.9% Sn, and 35.9% Ni.

[0046] Comparative Example 2

[0047] The difference between this comparative example and Example 1 is that only CuCl2·2H2O, SnCl2·2H2O, NiSO4·6H2O, Bi(NO3)3·5H2O (Cu 2+ Sn 2+ 、Ni 2+ 、Bi 3+ The molar ratio of the four metal ions is 1:1:1:1, and the total molar ratio of the four metal ions is 0.2 mmol), and the other conditions and steps are the same to obtain CuSnNiBi alloy powder, wherein Cu is 25.0%; Sn is 19.2%; Ni is 29.4%; and Bi is 26.4%.

[0048] Comparative Example 3

[0049] The difference between this comparative example and Example 1 is that only CuCl2·2H2O, SnCl2·2H2O, NiSO4·6H2O, FeCl2·4H2O (Cu 2+ Sn 2+ 、Ni 2+ and Fe 2+The molar ratio of the four metal ions is 1:1:1:1, and the total molar ratio of the four metal ions is 0.2 mmol), and the other conditions and steps are the same to obtain CuSnNiFe alloy powder, wherein Cu is 26.4%; Sn is 21.4%; Ni is 26.5%; and Fe is 25.6%.

[0050] Comparative Example 4

[0051] Weigh CuCl2·2H2O, SnCl2·2H2O, NiSO4·6H2O, Bi(NO3)3·5H2O, FeCl2·4H2O, (Cu 2+ Sn 2+ 、Ni 2+ 、Bi 3+ and Fe 2+ The molar ratio of the five metal ions is 0.2:1:1:1:1, and the total molar ratio of the five metal ions is 0.2 mmol), and the other conditions and steps are the same as those in Example 1 to obtain CuSnNiBiFe high entropy alloy powder, wherein Cu is 5.0%; Sn is 20.5%; Ni is 26.0%; Bi is 26.5%; and Fe is 22.0%.

[0052] Example 4

[0053] (1) CO2 electrocatalytic reduction performance test

[0054] Test method: A three-electrode system was used, with carbon paper loaded with electrocatalyst as the working electrode, ruthenium-iridium-titanium electrode as the counter electrode, and saturated Ag / AgCl electrode as the reference electrode; 0.5M KHCO3 solution was used as the electrolyte (pH 8.2); Nafion membrane was used as the ion-selective diaphragm; the electrocatalytic test potential was -1.4V (with Ag / AgCl as the reference electrode). The alloy nanopowders prepared in Example 1 and Comparative Example 2 were ultrasonically mixed with propanol / ethanol / water and Nafion solution as electrocatalysts, and then drop-coated on carbon paper as the working electrode to test the CO2 electrocatalytic reduction performance. The products were detected by gas chromatograph, and the contents of the main gas phase products are shown in Table 1.

[0055] Table 1

[0056]

[0057] From the data comparison in Table 1, it can be seen that when Comparative Example 2 only uses CuSnNiBi alloy, the total H2 and CO gas production is much lower than the gas production of CuSnNiBiFe high entropy alloy used in Example 1 of the present invention, indicating that the present invention improves the overall catalytic performance of the alloy through the synergistic effect of five metal elements.

[0058] (2) CO2 electrocatalytic reduction stability test

[0059] Test method: Test the current density fluctuation under a certain voltage (-1.3V (with Ag / AgCl as reference electrode) for 48 hours. Figure 4 As shown, using Example 1 as the catalyst, a stability test was conducted at a potential of -1.3 V (with Ag / AgCl as the reference electrode). The test current density did not change much within 48 hours, indicating that the catalyst had good stability.

[0060] (3) Detection of CO2 electrocatalytic reduction product types

[0061] like Figure 5 and Figure 6 As shown, the alloy nanopowders prepared in Example 1 and Comparative Examples 1 to 4 are used as catalysts to electrocatalyze the reduction of CO2 gas products at the same potential of -1.5V (with Ag / AgCl as the reference electrode). The main product components of the catalysis of Comparative Examples 1 to 4 are synthesis gas (H2+CO), but as the types of elements in the alloy powder increase, the types of products are more abundant. Only under the catalysis of high entropy alloy nanopowder CuSnNiBiFe can ethylene and ethane C2 products that are difficult to generate with traditional metal catalysts be generated. At the same time, through Figure 5 (d) and Figure 6 It can be seen from the comparison that when the content of copper in the alloy powder is not within the scope of the present invention, the synthesis gas mainly exists in the form of H2, and the contents of O2, N2 and CO are significantly reduced, indicating that there is a synergistic effect between the amounts of metal elements used.

Claims

1. A CuSnNi-based high entropy alloy nanopowder for CO2 electrocatalytic reduction, characterized in that: Calculated by the amount percentage of substances, it is composed of the following components: Cu 15-25%, Sn 15-25%, Ni 15-25%, Fe15-28%, Bi 15-28%; The high entropy alloy nanopowder is obtained by adding a protonic acid to a precursor solution to maintain an acidic condition, then adding a reducing agent to perform a reduction reaction, purifying and drying. The precursor solution is obtained by mixing and dissolving at least one of a ferric salt and a ferrous salt with a copper salt, a tin salt, a nickel salt and a bismuth salt; The CuSnNi-based high entropy alloy nanopowder is used as a catalyst for electrocatalytic reduction of CO2 to generate C2 products.

2. The CuSnNi-based high entropy alloy nanopowder for CO2 electrocatalytic reduction according to claim 1, characterized in that: The total concentration of all metal salts in the precursor solution is 10 -4 ~10 -1 mol L -1 .

3. The CuSnNi-based high entropy alloy nanopowder for CO2 electrocatalytic reduction according to claim 2, characterized in that: The molar ratio of the copper salt, tin salt, nickel salt and bismuth salt is 2+ Sn 2+ 、Ni 2+ and Bi 3+ The molar ratio is 1:(0.5-2):(0.5-2):(0.5-1); The molar ratio of the total molar amount of the ferric salt and the ferrous salt to the copper salt is 3+ and Fe 2+ Total molar amount and Cu 2+ The molar ratio is (0.5-2):

1.

4. The CuSnNi-based high entropy alloy nanopowder for CO2 electrocatalytic reduction according to any one of claims 1 to 3, characterized in that: The protonic acid comprises at least one of hydrochloric acid, hydrobromic acid, sulfuric acid, nitric acid and phosphoric acid, and the amount of the protonic acid is 1‰ to 10% of the total molar amount of metal ions in the metal salt; The acidic condition is to control the pH value to be 4-5.

5. The CuSnNi-based high entropy alloy nanopowder for CO2 electrocatalytic reduction according to claim 1, characterized in that: The reducing agent includes at least one of LiBH4, NaBH4 and KBH4, and the ratio of the amount of the reducing agent to the total molar amount of metal ions in the metal salt is (2-50):

1.

6. The CuSnNi-based high entropy alloy nanopowder for CO2 electrocatalytic reduction according to claim 5, characterized in that: The reduction reaction conditions are: temperature of -20 to 80°C and time of 0.5 to 8 hours.

7. A CuSnNi-based high entropy alloy nanopowder for CO2 electrocatalytic reduction according to claim 1, 2, 3, 5 or 6, characterized in that: The specific surface area of ​​the high entropy alloy nanopowder is 50 to 200 m 2 g -1 , particle size is 5 to 50 nm.

Citation Information

Patent Citations

  • High-entropy alloy and preparation method thereof, membrane electrode assembly and fuel cell

    CN116574957A

  • High-entropy alloy nano-particles, catalyst and application of high-entropy alloy nano-particles and catalyst

    CN117943535A